PERAN PENGURUS DALAM MENINGKATKAN KEDISIPLINAN BELAJAR SANTRI MADRASAH DINIYAH DI PONDOK PESANTREN MIFTAHUL HUDA MALANG - Ahmat Syarifudin (VICRATINA, 2019)
This research was conducted at the Pondok Pesanten Miftahul Hiuda Malang which began in June 2019. In this atudy we used the method of observation, interviews and documentation. The methods of analyzing data is by reducing data, presenting data and drawing conclusions. The functions of the management of the Pondok Pesantren Miftahul Huda Malang as administrators and as a model for uswatun hasanah for santri, the responsibility of board adminstrators as a discipline for santri, administrators, and so om head of management, secretary of management, manager of treasurer, administrator of the secretary, and planner of learning tarbiyah and ta’limKata Kunci : Peran Pengurus, Kedisiplinan Belajar, Santri